Kingdom of Netherlands : Netherlands; Selected Issues and Analytical Notes. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
Important issues of the Netherlands are discussed. Openness to trade has benefited the Netherlands before the crisis and has supported the recent recovery process. However, both financial openness and trade linkages have also been a transmission channel for the financial crisis. Synchronized fiscal tightening across Europe has important spillover effects for GDP growth. The improvement on the supply side of credit has contributed to a normalization of the credit market. However, the recent increase in the financial stress index indicates that the situation is still fragile.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet